The Effectiveness of Schema Therapy Focused on Mindset on Self-Esteem and Impulsivity in Individuals with Narcissistic Personality Disorder - Mohseni, Fatemeh; Bibak, Fatemeh (Health Nexus, 2023)
In the complex world of clinical psychology, narcissistic personality disorder is recognized as a problem that can impact various aspects of an individual’s personal and social life. The current study aimed to determine the effectiveness of schema therapy focused on mindset on self-esteem and impulsivity in individuals diagnosed with narcissistic personality disorder. This quasi-experimental research was conducted with a pre-test, post-test, and follow-up design, including a control group. The population of the study comprised all individuals visiting counseling centers in Bushehr who were diagnosed with narcissistic personality disorder by psychiatrists or clinical psychologists. The sample included 30 individuals, selected through purposive sampling and randomly assigned into two groups of 15 each, experimental and control. Data were collected using the Coopersmith Self-Esteem Inventory, Narcissistic Personality Inventory, and Barratt Impulsiveness Scale, and analyzed using repeated measures analysis of variance with SPSS software version 26. The results showed significant differences between the mean scores of pre-test, post-test, and follow-up for variables of impulsivity and self-esteem (P < .01). Schema therapy significantly altered the post-test and follow-up scores compared to the pre-test (P < .01), and these changes persisted during the follow-up period. It can be concluded that schema therapy focused on mindset is effective in enhancing self-esteem and reducing impulsivity among individuals with narcissistic personality disorder, suggesting its utility in addressing issues in narcissistic individuals.